Mode II fatigue crack growth properties of adherends bonded with DP8005: End–notched flexible tests. (June 2018) - Kim, Hyun-Bum; Naito, Kimiyoshi; Oguma, Hiroyuki
Highlights: A faster destructive effect occurred under Mode II fatigue tests than that occurring in Mode I fatigue tests. The values of Δ GII.th for the aluminum alloy, GF/PP, and CF/EP specimens for the ENF fatigue tests were 258.7, 288.6, and 323.9 Jm −2, respectively. The fracture surfaces for the aluminum alloy, GF/PP, and CF/EP specimens were cohesive dominant failures. Δ GII.th of adherends bonded with DP8005 under mixed−mode loading can be approximately estimated by using only the fracture toughness value. Abstract: Using end–notched flexible (ENF) tests, this study investigates the Mode II fatigue crack growth properties of adherends bonded with a DP8005 acrylic–based adhesive. The experimental results obtained from the ENF fatigue tests were compared with the results from the double cantilever beam (DCB) fatigue tests to obtain comprehensive fracture properties for DP8005. By comparing the slopes defined by the Paris law, a faster destructive effect was observed in ENF fatigue tests compared with that observed during the DCB fatigue tests. The study demonstrates that engineers and/or designers can estimate the threshold energy release rate range using only fracture toughness under mixed–mode loading.